Giant Intrathoracic Desmoid Tumor – a Case Report - Cunha, Sara (2024)
Desmoid tumors are soft tissue neoplasms arising from fascial and muscle-aponeurotic structure. These tumors are locally aggressive and have a high recurrence rate, even after complete resection. We present the case of a female with a giant intrathoracic desmoid tumor. She underwent complete surgical resection with no disease recurrence. Desmoid tumors’ natural history is not well defined and is often enigmatic, making these tumors difficult to manage. Currently, for intrathoracic desmoid tumors, medical treatment is the recommended approach, nevertheless, surgery can be considered in selected patients.